1997
DOI: 10.1051/rnd:19970506
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cholecystokinin concentrations in 3-day-old lambs: effect of the duration of fasting preceding a sucking bout

Abstract: Summary -Cholecystokinin (CCK) is a regulatory peptide released into the circulation after the ingestion of food. Our knowledge concerning the factors affecting its pattern of secretion in the mammalian neonate is scanty. Therefore, in this work we studied plasma concentrations of CCK in 3-dayold lambs after a sucking bout that followed either a short (2 h) or a long fasting period (9 h). Plasma concentrations of CCK were measured by radioimmunoassay in blood samples collected from jugular veins 10 min before,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In addition, OT levels may also be elevated through the effect of endocrine factors such as the secretion of the gastrointestinal hormone CCK. This could well be the case in the lamb since CCK is released after suckling ( 30 , 33 ) and it is known, in the rat, that both CCK and gastric distension activate the oxytocinergic system in the hypothalamus, and trigger the release of OT in the plasma ( 71 , 72 ). Preliminary data from Experiment 2 demonstrate that OT concentrations also rise in the cerebrospinal fluid after bottle-feeding, and that the phenomenon is quite repeatable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, OT levels may also be elevated through the effect of endocrine factors such as the secretion of the gastrointestinal hormone CCK. This could well be the case in the lamb since CCK is released after suckling ( 30 , 33 ) and it is known, in the rat, that both CCK and gastric distension activate the oxytocinergic system in the hypothalamus, and trigger the release of OT in the plasma ( 71 , 72 ). Preliminary data from Experiment 2 demonstrate that OT concentrations also rise in the cerebrospinal fluid after bottle-feeding, and that the phenomenon is quite repeatable.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that ingesting colostrum in the hours after birth is a key factor for the development of a preference for the mother ( 31 , 32 ). The neonatal suckling activity triggers the release of cholecystokinin (CCK) in the blood, a gastrointestinal hormone which activates vagal afferent fibres and the brain stem ( 33 , 34 ). Blocking the cholecystokininergic system with a specific antagonist that binds to peripheral receptors at birth prevents the development of a preference for the mother ( 35 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma concentrations of ghrelin in fasting humans, rats and ruminants are higher than non-fasting humans and animals (Kojima & Kangawa 2005;Wertz-Lutz et al 2006). In addition, plasma CCK levels of fasting rats (Kanayama & Liddle 1991), 3-day-old lambs (Nowak et al 1997) and humans (Ohgo et al 1988) were low. Therefore, basal plasma ghrelin and CCK levels between fasting conditions and non-fasting conditions are different.…”
Section: Introductionmentioning
confidence: 97%
“…2006). In addition, plasma CCK levels of fasting rats (Kanayama & Liddle 1991), 3‐day‐old lambs (Nowak et al . 1997) and humans (Ohgo et al .…”
Section: Introductionmentioning
confidence: 99%
“…By the age of 24 hr, lambs show a strong preference for their mothers over alien ewes (Nowak, 1990), an ability depending mainly on experiencing the first suckling interactions, in addition to visual and auditory cues (Nowak, 1991; Nowak, Murphy, et al, 1997). Nowak, Orgeur, et al (1997) showed that suckling was followed by a significant increase of plasma CCK levels over the 20–50-min period assessed postsuckling. Furthermore, only lambs whose CCK plasma levels increased in the first 6 postnatal hours displayed a preference for their mothers at 24 hr (Nowak, Murphy, et al, 1997).…”
mentioning
confidence: 96%